2023
DOI: 10.1587/elex.20.20230054
|View full text |Cite
|
Sign up to set email alerts
|

Advanced dry etching of GaAs/AlGaAs multilayer wafer with InAs quantum dot for circular defect in photonic crystal laser

Abstract: We previously proposed the circular defect in two-dimensional photonic crystal (CirD) laser based on a GaAs/AlGaAs multilayer wafer, which is fabricated by dry etching. This CirD laser uses InAs quantum dot (QD) layers as the gain medium, but this inhibits vertical dry etching. We improved the dry etching process by introducing three QD layers and threestep dry etching for fabricating the CirD laser. As a result, CirD structures with good etching profiles could be fabricated and excellent optical properties we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…The previous study on the CirD laser fabricated by three-step dry etching reported a threshold of about 50 μW. [17] This result indicates that one-step dry etching can fabricate samples with characteristics equivalent to those of threestep dry etching. Figure 6b shows the spectrum measured by the PD array over a 50 nm span with an input power of 238 μW, which is the point in Figure 6a measured at the highest input power.…”
Section: Optical Measurementmentioning
confidence: 82%
See 1 more Smart Citation
“…The previous study on the CirD laser fabricated by three-step dry etching reported a threshold of about 50 μW. [17] This result indicates that one-step dry etching can fabricate samples with characteristics equivalent to those of threestep dry etching. Figure 6b shows the spectrum measured by the PD array over a 50 nm span with an input power of 238 μW, which is the point in Figure 6a measured at the highest input power.…”
Section: Optical Measurementmentioning
confidence: 82%
“…In the second step, the etching progress was accelerated by reducing the CH 4 flow rate (see Table S1 of ref. [17]). However, the three‐step etching method poses a problem for future device fabrication: the etching rates differ greatly between drainage trench (see Figure S2 of ref.…”
Section: Introductionmentioning
confidence: 99%
“…This value is close to the threshold power of 50 μW obtained in our previous study for a well‐lased sample with the same epitaxial layers as that used in this study. [ 28 ] Although the sample in the previous study was fully oxidized, the w ox of this particular sample is already sufficiently large, resulting in a comparably low threshold power. Figure 4b,c shows the spectra of span = 50 nm and span = 2 nm for this sample, where the input power is 238 and 51 μW, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…電子ビームリソグラフィ(EBL)は ,最小ビーム径 2 nm 程度の電子ビームを走査してレジストを露光するリソ グラフィ技術の一つである.ナノスケールの微細加工を可能とするため,主に電子回路の集積化など半導体分野 で発展し,現在では光学デバイス (Tanaka et al, 2016)や量子デバイス (Kato et al, 2021;Houck et al, 2021;Adachi et al, 2023) ,バイオチップ (Taniguchi et al, 2020)など様々な分野で用いられている.EBL で作製したレジストパ ターンの多くは後工程でエッチングやリフトオフのマスクとして利用され,露光上面から 2 次元的に観察したと きに所望の線幅やホール径を有しているかを重要としてきた. 近年の高ビーム強度あるいは高加速電圧の EBL 装置によって, 比較的厚膜のレジストを用いた精細なパターニ ングが可能となり,そのようなレジストパターンをナノインプリントのモールドやナノトランスファプリントの スタンプの原型として利用することで,EBL で作製しなければ到達できないナノスケールのパターンを高スルー プットに複製する手法が試みられている (Taniguchi and Goto, 2018;Barcelo et al, 2016;Oh et al, 2021) .特にナノイ ンプリントモールドの作製において,その側壁傾斜角が形状精度や歩留まりに影響を及ぼすことが示されている (Sung et al, 2010;Fang et al, 2014) .例えば,モールドの離型性は,その側壁角度と離型に要する力に強い相関が あり,傾斜角が 90˚から約 75˚まで減少するにつれて離型に要する力が減少する (Hirai et al, 2015) .ナノトラン スファプリントに用いるスタンプでも,側壁角度は転写する薄膜の離型性に重要と考えられる.そのため,それ らの原型となるレジストパターンはこれまで重要としてきた線幅やホール径などの 2 次元的な形状に加えて,断 面形状を含む 3 次元的な検討が必要と考えられる. EBL で得られるレジストパターンは,同一の露光パターンであっても,加速電圧,レジストの化学特性(コン トラスト) ,現像方法,およびドーズ量などで変化する.3 次元形状を作製するグレースケール EBL と呼ばれる 技術があり, ブレーズド形状や階段形状の作製が可能である (Grigaliūnas et al, 2016;Kirchner and Schift, 2019;Chen et al, 2020;Mortelmans et al, 2020)…”
Section: 緒 言unclassified